Gender-associated analysis of high-risk groups for mental health problems in law-enforcement officers - Omelyanovich, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
Background. Mental disorders prevention in specific professional groups is impossible without scientifically substantiated allocation of groups with increased neuropsychiatric and psychosomatic disorders risk. This fact indicates the need to study the gender, age and professional characteristics in law enforcement workers who already have problems with psychological adaptation. Methods and materials. The study involved 1630 law enforcement officers (1,301 men and 329 women) who were evaluated with the Symptom Checklist-90-R (SCL-90-R). As the statistical methods were used the partial regression calculation coefficient η2, cohort calculation risk measures, φ*-total Fischer transformation method, and single-factor dispersion Fisher’s analysis. Results. According to gender characteristics, the problems with psychological adaptation in men were significantly less pronounced than in women (φ*=1.79; p=0.37). These data were confirmed by the cohort calculation and risk measures results: men – 0.261, women – 0.349 (the psychological disadaptation risk in women was 1.3 times higher than men). There weren’t any statistically significant age differences between the representatives of both gender groups with psychological adaptation disturbances and healthy ones (φ* ≤1.19; p≥0.1). Among patients who suffered from psychosomatic diseases, were men over the age of 35 (φ* ≥2.28; p≤0.0001) and women over 26 years old (φ*= 2.16; p=0.014) prevailed. There were significantly fewer people among men with psychosomatic illnesses with 4-9 years of professional working experience than in a healthy group. On the contrary, there were significantly more patients in a law enforcement workers group with 10-15 years working experience than in the healthy one (φ*>1.73; p<0.0001). Conclusion. The risk of mental health problems in female police officers is much higher than in men. Disadaptation development is not related to the age and length of working experience in the police. Men with working experience greater than 10 years should be included in the risk group for psychosomatic diseases.